The effect of -COOH functionalized carbon nanotube doping on electro-optical, thermo-optical and elastic properties of a highly polar smectic liquid crystal - Cetinkaya, M.C.; Yildiz, S.; Ozbek, H. (Elsevier BV, 2018)
Abstract We investigate in this work the effect of carboxyl group (-COOH) functionalized multi-walled carbon nanotubes (f-MWCNTs) on physical properties of a highly polar smectic liquid crystal octyl cyanobiphenyl (8CB). We report new experimental data of the temperature variation of optical birefringence, dielectric anisotropy, electrical conductivity anisotropy, threshold voltage, splay elastic constant, voltage-on and voltage-off response times, and also rotational viscosity of 8CB-f-MWCNT composites. It has been observed that the inclusion of f-MWCNT substantially decreases both the nematic-isotropic and the nematic-smectic A transition temperatures compared to 8CB host. We have observed that the splay elastic constant increases with f-MWCNT loading which can be attributed to the strong elastic interaction between f-MWCNTs and 8CB molecules due to -COOH surface functionalization. It has been further shown that -COOH functionalization of MWCNT triggers the enhancement in nematic ordering for lower f-MWCNT contents while higher contents would result in disordering effect of the orientational order of the medium. Based on response time measurements, we have concluded that the inclusion of f-MWCNTs into 8CB host causes the optical relaxation process to slow down and then increases the rotational viscosity of the composites. We have documented that while all f-MWCNT doped composites exhibit the expected temperature dependencies of their physical properties, their dependence on f-MWCNT content is still controversial.